Effect of hormonal and herbal therapy at calving on postpartum estrus and fertility response and serum hormonal profile in crossbred cows - Parmar, Sanjaykumar Chamanbhai (Indian Journal of Dairy Science, 2016)
The study was conducted on 24 HF crossbred parturient cows to evaluate the effect of hormonal and herbal preparations on postpartum estrus response and serum progesterone and oestradiol-17β profile. The cows were randomly divided into four groups, each of 6 animals. The cows in Gr-I and Gr-II were injected with Methyl ergometrine (5 mg) and Dinoprost tromethamine (PGF2α, 25 mg) i/m, respectively immediately after parturition, while the cows of Gr-III received Utrovet tablets (10 tab, bid, PO) for first 10 days postpartum, and those of Gr-IV received 5 ml normal saline i/m and served as control. Overall, 83.33 per cent (5/6) cows in each Gr-I and Gr-II exhibited first postpartum estrus within mean intervals of 36.33 ± 1.17 and 26.50 ± 0.85 days, respectively, while in Gr-III and Gr-IV, 66.67 per cent (4/6) and 50.0 per cent (3/6) cows expressed postpartum estrus with mean intervals of 39.00 ± 2.84 and 48.00 ± 2.39 days, respectively. The postpartum estrus interval was significantly (P